Role of laboratory experience in the teaching of clothing and textiles in secondary schools in delta state: it’s impact in entrepreneurship skills - Abamba, Deborah Chibuzor; Arubayi, Diana Oritsegbubemi; Azonuche, Juliana Ego (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of the study was aimed at finding out the role of laboratory experience in the teaching of clothing and textiles in secondary schools in Delta State and its impact in entrepreneurship skills. Four Research questions were formulated to guide the study. The population was all students studying clothing and textile in Delta state. All the 264 respondents were used for the study. Questionnaire was the instrument used for data collection and data were analyzed with mean and standard deviation. Finding showed that identify the laboratory roles in the teaching of Clothing and textiles to include; to develop practical competence, identify tools and materials, demonstrate proper usage of tools and equipment, and identify students’ strengths and weaknesses. Also its effectiveness helps students in problem solving, increase interest, strengthen their ability for critical thinking and solve problems, thereby boost entrepreneurship skills through teamwork, creativity and innovation for self reliance. Conclusions and recommendations were made; that to prepare students for a better career future, the method of teaching adopted by the teacher plays an important role in continuity and advancement of clothing and textile as a course of study. Government should provide modern laboratories and equipment and subsidize practical expenses for the student in schools.